(untitled) - Ralston, Anthony (New York, 1965)
his outstanding text by two well-known authors treats numerical analysis with mathematical rigor, but presents a minimum of theorems and proofs. Oriented toward computer solutions of problems, it stresses error analysis and computational efficiency, and compares different solutions to the same problem.
Keywords: Numerical analysis,Phân tích số